Peran Remaja dalam Keluarga di SMPIT Nurul Ilmi Kota Jambi - Indrawati, Iin; Hesty, Hesty; Hidayat, Muhammad; Novitasari, Maryam (Jurnal Abdimas Kesehatan (JAK), 2025)
A teenager must be able to carry out his role in family development tasks. The condition of adolescents who attend SMPIT Nurul Ilmi mostly come from well-off families and tend to live with being served in terms of taking care of themselves. This condition is feared to have an impact on the thinking and behavior of adolescents who tend to be less independent, thinking that they still have parents who will help them and solve their problems. The purpose of this activity is for adolescents to understand their role in the family so that they are able to become strong, independent, responsible and have a leadership spirit. The activity was carried out on November 1, 2022 at SMPIT Nurul Ilmi Jambi. The implementation method used is the direct face-to-face method with participants to provide health education by means of face-to-face, discussion and combined with the EMO-DEMO technique. The expected contribution from participants is that all participants participate in all series of activities so that they can provide optimal activity results. The result of this activity is that students as adolescents become more understanding of their role in the family, seen from the reactions that arise after the activity adolescents write down all their wishes for the future and promise to be responsible humans, protect and love their families wholeheartedly. Interested parties such as schools, teachers and parents can continue the condition of students who begin to open themselves to be responsible for themselves, their families and the nation. Sharpen adolescents' awareness, independence, discipline and increase compassion for their families and environment.